mTORC1-dependent increase in oxidative metabolism in POMC neurons regulates food intake and action of leptin - Magalie Haissaguerre; Amandine Ferrière; Vincent Simon; Nicolas Saucisse; Nathalie Dupuy; Caroline André; Samantha Clark; Omar Guzman-Quevedo; Antoine Tabarin; Daniela Cota (Elsevier, 2018)
Objective: Nutrient availability modulates reactive oxygen species (ROS) production in the hypothalamus. In turn, ROS regulate hypothalamic neuronal activity and feeding behavior. The mechanistic target of rapamycin complex 1 (mTORC1) pathway is an important cellular integrator of the action of nutrients and hormones. Here we tested the hypothesis that modulation of mTORC1 activity, particularly in Proopiomelanocortin (POMC)-expressing neurons, mediates the cellular and behavioral effects of ROS. Methods: C57BL/6J mice or controls and their knockout (KO) littermates deficient either for the mTORC1 downstream target 70-kDa ribosomal protein S6 kinase 1 (S6K1) or for the mTORC1 component Rptor specifically in POMC neurons (POMC-rptor-KO) were treated with an intracerebroventricular (icv) injection of the ROS hydrogen peroxide (H2O2) or the ROS scavenger honokiol, alone or, respectively, in combination with the mTORC1 inhibitor rapamycin or the mTORC1 activator leptin. Oxidant-related signal in POMC neurons was assessed using dihydroethidium (DHE) fluorescence. Results: Icv administration of H2O2 decreased food intake, while co-administration of rapamycin, whole-body deletion of S6K1, or deletion of rptor in POMC neurons impeded the anorectic action of H2O2. H2O2 also increased oxidant levels in POMC neurons, an effect that hinged on functional mTORC1 in these neurons. Finally, scavenging ROS prevented the hypophagic action of leptin, which in turn required mTORC1 to increase oxidant levels in POMC neurons and to inhibit food intake. Conclusions: Our results demonstrate that ROS and leptin require mTORC1 pathway activity in POMC neurons to increase oxidant levels in POMC neurons and consequently decrease food intake. Keywords: Hypothalamus, Reactive oxygen species, mTORC1, Leptin, Food intake, POMC